Antifungal Activity of Semecarpus anacardium Linn. Oil against Four Phytopathogenic Fungi - Patil, Aarti; Quazi, Sadat (Plantae Scientia, 2019)
The present study was undertaken to evaluate in-vitro antifungal activity of Semecarpus anacardium Linn. oil against four fungal pathogens, viz. Curvularia penniseti, Curvularia lunata, Fusarium oxysporum f. sp. ciceris and Helminthosporium maydis using poisoned food technique. The DMSO extract of S.anacardium oil was found to be more or less active against almost all tested pathogenic fungi with a varied spectrum of reduced growth. C.lunata has shown 93.3% inhibition and F.oxysporum and H.maydis have shown 94.4% inhibition and 100% mycelial inhibitions at 15% and 18% concentrations of the extract respectively. Whereas, C.penniseti was found to be quite sensitive that showed 88.9 inhibitions at 10% concentration but it showed 100% inhibition at 18% concentration.